A Cost-Effectiveness Analysis of Comprehensive Smoking-Cessation Interventions Based on the Community and Hospital Collaboration - Qin, Tingting; Jin, Qianying; Li, Xingming; Bai, Xinyuan; Qiao, Kun; Gu, Mingyu; Wang, Yao (Frontiers in Public Health, 2022)
Background: Prevalence of cigarette smoking in China is high and the utilization of smoking cessation clinics is very low. Multicomponent smoking cessation interventions involving community and hospital collaboration have the potential to increase smoking cessation rate. However, the cost-effectiveness of this intervention model is unknown. Methods: We conducted a smoking cessation intervention trial in 19 community health service centers in Beijing, China. A cost-effectiveness analysis was performed from a societal perspective to compare three strategies of smoking cessation: no intervention (NI), pharmacological intervention (PI) and comprehensive intervention (CI) (PI plus online health promotion). A Markov model, with a time horizon of 20 years, was used to simulate natural progression of estimated 10,000 male smokers. A cross-sectional survey was conducted to obtain data on costs and quality adjusted life years (QALYs) by using the five-level EuroQol-5-dimension (EQ-5D-5L) questionnaire. Probabilistic sensitivity analysis was performed to explore parameters of uncertainty in the model. Results: A total of 680 participants were included in this study, including 283 in the PI group and 397 in the CI group. After 6 months follow-up, the smoking cessation rate reached 30.0% in the CI group and 21.2% in the PI group. Using the Markov model, compared with the NI group, the intervention strategies of the PI group and the CI group were found to be cost-effective, with an incremental cost-effectiveness ratio (ICER) of $535.62/QALY and $366.19/QALY respectively. The probabilistic sensitivity analysis indicated that the CI strategy was always the most cost-effective intervention. Conclusion: CI for smoking cessation, based in hospital and community, in China is more cost-effective than PI alone. Therefore, this smoking cessation model should be considered to be implemented in healthcare settings.